The role of hat in the self-identification of Latin American peoples - Iu. V. Davtian (Ибероамериканские тетради, 2023)
The diversity of Latin American hats is determined by the climatic and geographical characteristics of the area of residence of different nations, as well as socio-economic factors, however, inter-ethnic ties play a key role, as well as the historically accumulated cultural experience of the ethnic group, which is reflected in the national costume. The purpose of this study is to substantiate the thesis that the headdress, in addition to protective, informational, aesthetic and other functions, has a function of self-identification and, as a result, an educational function, which consists in transfering from generation to generation the knowledge about national culture and history, as well as in the formation in the subconscious of younger generations of ethnodifferentiating and ethno-consolidating signs. To achieve this goal, methods of description, comparison and observation, classic for cultural research, as well as a hypothetical-deductive method are used. Studying the history of the emergence and peculiarities of hat-wear in a number of countries in Latin America, as well as comparing them with each other, it is concluded that the Latin American hats concentratively reflects the worldview of the people. It is a kind of cultural metasymbol, through which the transfer of spiritual values takes place and the mechanism of ethnocultural self-identification of the people is preserved. Being an element of the national costume, one of the forms of public consciousness, it reflects reality, but in a special way, being a carrier of both national and personal, as well as class cultural values. Wearing a hat is not just a tradition for Ecuadorians, Bolivians, Mexicans, Colombians and other peoples of the region. The headdress represents a symbol of the commonality of the nation.